Brother's keeper : the United States, race, and empire in the British Caribbean, 1927-1962 - Parker, Jason C. (Oxford University Press, 2008)
This is an international history of Anglo-American-Caribbean relations, including the role of the African diaspora, during the long decolonization of the British Caribbean. The author explains why a policy of American restraint was exercised, despite the long association of West Indians with black radicalism in the US.